Training Needs for Emerging Infectious Diseases Research, Surveillance and Control in High-Risk and Resource-Constrained Settings: Findings and Recommendations for Uganda - Asingura, Bannet; Kiweewa, Francis; Kaawa-Mafigiri, David; Achabo, Sheila; Mimbe, Derrick; Okullo, Allen Eva; Eyu, Patricia; Nanyondo, Jauhara; Naluyima, Prossy; Kandole, Martha; Tindikahwa, Allan; Nalunga, Justine; et al. (ResearchSquare, 2022)
Uganda is prone to Emerging Infectious Diseases (EIDs) which can cause serious epidemics and pandemics. Uganda’s capacity for EID research, surveillance and control is improving but still low partly due to inadequate highly knowledgeable and skilled human and animal health workers. To inform the design of training programs that can address Uganda’s health workforce capacity gaps, we conducted a training needs assessment.A qualitative study involving a desk review, 25 key informant interviews and a 1-day consultative workshop to review study findings.The majority of infectious disease research, surveillance and control in Uganda focuses on HIV/AIDS, Tuberculosis, Malaria and viral hemorrhagic fevers e.g., Ebola and Marburg. Health workforce capacity for surveillance and control is robust compared to many other resource-constrained settings but research capacity and output are relatively low, especially for EIDs. Public and private tertiary institutions in Uganda predominantly offer training in primary health care and population studies through problem-based learning, community-based education and services, and Blended Learning (BL). There are several training programs in advanced clinical and epidemiological sciences, but few opportunities in biomedical sciences (e.g. virology, immunology, bioinformatics and predictive modeling), social sciences, One Health and leadership. To address the gaps, the following interventions were recommended: 1) advanced graduate and/or post-graduate training in basic biomedical sciences; 2) short-term training for continuous knowledge and skills development in multidisciplinary/One Health approaches; and 3) pedagogy and mentorship through BL, networking and experiential training programs that effectively leverage North-South collaborations. Training and mentorship should be achieved by (a) conducting most of the in-person didactic and experiential training at Southern tertiary and research institutions, (b) utilizing electronic-learning for didactic training and mentor-mentee interactions with subject-matter experts at Northern institutions, and (c) well-orchestrated placements at Northern institutions for hands-on experience using the latest advances in science and technology.Inadequate health workforce capacity for EID research was identified as a priority gap that requires long and short-term multidisciplinary training interventions. Efficiently leveraging North-South collaborations for e-learning, short-term placements and mentorship will enable Uganda to remain abreast with latest advances in science and technology for EID research, surveillance and control.
Keywords: Training Needs; Emerging infectious diseases; Research; Surveillance